2022
DOI: 10.17358/ijbe.8.1.82
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Advertising: Men's Cognitive React to Women's Appeal

Abstract: Previous studies have stated that the women's appeal has been proven effective in gaining recognition necessary to enhance the popularity. The local gadget store in Bali has proved that the strategy is adequate to gain the name and popularity for their business. However, the findings show that although it succeeds in gaining recognition from society, it does not directly affect the intention to buy. This research attempts to reveal the perception of men towards the women in advertisements and whether it will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…On the other hand, FOMO is defined as the widespread concern of the individual being able to have rewarding experiences in social networks, and it found that FOMO significantly increases the level of depression and anxiety by increasing compulsive digital media platform use significantly (Dhir et al, 2018;Dossey, 2014). Therefore, purchase intention is believed to be raised by consumers to buy or not to buy a product based on the results of their evaluation and consideration of the product to determine the product is suitable for purchase (Yoga & Putri, 2022). H6: Higher FOMO will increase purchase intention.…”
Section: Purchase Intentionmentioning
confidence: 99%
“…On the other hand, FOMO is defined as the widespread concern of the individual being able to have rewarding experiences in social networks, and it found that FOMO significantly increases the level of depression and anxiety by increasing compulsive digital media platform use significantly (Dhir et al, 2018;Dossey, 2014). Therefore, purchase intention is believed to be raised by consumers to buy or not to buy a product based on the results of their evaluation and consideration of the product to determine the product is suitable for purchase (Yoga & Putri, 2022). H6: Higher FOMO will increase purchase intention.…”
Section: Purchase Intentionmentioning
confidence: 99%